Labor competencies and shared values with approaches in workers of the Physical Culture Faculty of Guantanamo - Yudania Rodríguez-García; Gilberto García-González; Kobel Guerrero-Mugercia (Universidad de Guantánamo, 2019)
In the research, shared values and labor competences are linked with incidence for all teachers and managers. Its objective is to enable skills and abilities in the field of securities and competency management for managers and other entities, human resource managers in particular, consultants, researchers and trainers, for their effective and efficient introduction in the practice of educational organizations for the achievement of competitiveness. For the realization of this work, theoretical methods such as analysis-synthesis, induction-deduction, historical-logical and the dialectic were applied. From the empirical level, observation, interview and survey were used.